A Survey : Application of Big Data in the Travel and Tourism Industry - Putri Previa Yanti (Pusat Teknologi Informasi dan Pangkalan Data IAIN Syekh Nurjati Cirebon, 2020)
The development of information technology has increased the travel and tourism industry. The travel and tourism data are available in many sources such as telephone, social media, sensor system on the internet of things, and others. The application of big data has great potential in the development of the travel and tourism industry. Big data can take advantage of new things in making the right decisions and seeing opportunities in doing better business. This paper provides a survey that discusses big data in the travel and tourism industry. Big data is used to ticket price and demand prediction. In addition, big data is also used to build a tourism plans and recommender system with the personalized and adaptive method. Combination of using the internet of things and big data can help the industry to price their product. The result of this study is some of the implementation of big data in the travel and tourism industry. We conclude that big data can be used to explore new things in making the right decisions, seeing opportunities more observant, and doing business more efficiently